High-strength and high-thermal-conductivity magnesium alloy and preparation method thereof

By adding Cu, Si, Ag and Co elements to the magnesium alloy and carrying out specific heat treatment and extrusion processes, a high-strength and high thermal conductivity magnesium alloy is solved, and the problem of insufficient mechanical properties and thermal conductivity of existing magnesium alloys is solved. Suitable for high temperature environments and cutting-edge fields.

CN119121017APending Publication Date: 2024-12-13CENT SOUTH UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411309747.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing magnesium alloys cannot meet the high requirements in cutting-edge fields such as aerospace in terms of mechanical properties and thermal conductivity, and have low strength and poor thermal conductivity.

Method used

Using a high-strength and high-thermal conductivity magnesium alloy containing microalloyed elements Cu, Si, Ag and transition element Co, it forms Mg2Cu, Mg2Si, Mg2Co and Mg-Ag eutectics by controlling the content of Cu, Si, Ag and performing interrupted aging treatment. Improve the strength and thermal conductivity of the alloy, and improve the mechanical properties of the material through extrusion molding and solution treatment.

Benefits of technology

It realizes high strength (tensile strength ≥400MPa), high thermal conductivity (140~145W/(m·K) and excellent wear resistance of magnesium alloys. It is suitable for high temperature environments and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121017A_ABST
    Figure CN119121017A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength and high-thermal-conductivity magnesium alloy which comprises the following components in percentage by mass: 5.8 to 6.4 percent of Al, 2.8 to 3.3 percent of Cu, 0.9 to 1.2 percent of Zn, 4.4 to 5.8 percent of Si, 1.2 to 2.4 percent of Co, 1.3 to 2.0 percent of Ag and the balance of Mg and inevitable impurity elements. The alloy is high in strength, good in performance and excellent in heat conduction performance, and has great application value for achieving integration of magnesium alloy structures and functions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of magnesium alloy development, and in particular relates to a high-strength and high-thermal-conductivity magnesium alloy and a preparation method thereof. Background Art

[0002] Magnesium alloys are now widely used in aerospace, automobile, medical equipment, batteries and other fields due to their excellent properties such as low density, high specific strength, good damping and biocompatibility. The motor housing in traditional automobiles and other fields is usually an aluminum alloy motor housing, while magnesium alloys are currently used as a new type of metal material in the preparation process of motor housings due to their lightweight characteristics. However, the poor mechanical properties and thermal conductivity of traditional magnesium alloys cannot match the high requirements for material performance in cutting-edge fields such as aerospace and communication engineering.

[0003] The thermal conductivity of pure magnesium is 1.55 W∙(m∙K) -1 , the strength is about 10MPa; after alloying, the strength is greatly improved and the thermal conductivity is significantly reduced. For example, according to the American Magnesium and Alloy Handbook, the tensile strength of the magnesium alloy AZ81 containing aluminum and zinc is 275Mpa, and the thermal conductivity at 20℃ is 51.1 W∙(m∙K) -1 : Rare earth magnesium alloy WE43, with a strength of 250Mpa and a thermal conductivity of 51.3 W∙(m∙K) at 20°C -1 ; Magnesium alloy ZE41 containing zinc and rare earth has a tensile strength of 205Mpa and a thermal conductivity of 123.1 W∙(m∙K) at 20°C -1 ; Magnesium alloy ZC63 containing zinc and copper has a tensile strength of 210Mpa and a thermal conductivity of 122 W∙(m∙K) at 20°C -1 ; The magnesium alloy QE22 containing silver and rare earth has a tensile strength of 260Mpa and a thermal conductivity of 113 W∙(m∙K) at 20°C -1 The strength of the existing magnesium alloys with high thermal conductivity, such as ZE41 and QE22, is less than 265Mpa; while the thermal conductivity of the relatively strong magnesium alloys, such as AZ81 and WE43, is less than 55 W∙(m∙K). -1 .

[0004] Therefore, existing magnesium alloys cannot meet the requirements of high thermal conductivity and high strength in terms of thermal conductivity and mechanical properties. Summary of the invention

[0005] The object of the present invention is to overcome at least one disadvantage of the prior art and to provide a high-strength and high-thermal conductivity magnesium alloy and a preparation method thereof.

[0006] The technical solution adopted by the present invention is: In a first aspect, the present invention provides a high-strength and high-thermal-conductivity magnesium alloy, wherein the composition of the magnesium alloy is, by mass percentage, 5.8% to 6.4% Al, 2.8% to 3.3% Cu, 0.9% to 1.2% Zn, 4.4% to 5.8% Si, 1.2% to 2.4% Co, 1.3% to 2.0% Ag, and the remainder is Mg and unavoidable impurity elements.

[0007] In some examples, the Si content is 4.8-5.2% by mass.

[0008] In some examples, the content of the transition element Co is 1.9-2.2% by mass.

[0009] In some examples, the Ag content is 1.6-1.8% by mass.

[0010] In some examples, the alloy has a composition, by mass percentage, of Al 5.8-6.4%, Cu 2.8-3.3%, Zn 0.9-1.2%, Si 4.8-5.2%, Co 1.9-2.2%, Ag 1.6-1.8%, and the remainder is Mg and unavoidable impurity elements.

[0011] In some examples, the alloy has a composition of Al 5.99%, Cu 3.20%, Zn 1.19%, Si 5.28%, Co 2.04%, Ag 1.74%, and the balance is Mg and inevitable impurity elements.

[0012] In some examples, the high-strength copper-containing magnesium alloy has a yield strength of ≧320 MPa, a tensile strength of ≧400 MPa, an elongation of ≧20%, a corrosion rate of ≤0.25 mm·y-1, a room temperature thermal conductivity of 140 to 145 W / (m·K), and a density of approximately 1.8 g / cm3.

[0013] In a second aspect, the method for preparing a high-strength and high-thermal-conductivity magnesium alloy provided in the first aspect of the present invention comprises the following steps: 1) weighing raw materials in proportion for smelting at a smelting temperature of 740° C. to 780° C., removing slag and stirring uniformly; 2) Refining is performed under protective atmosphere conditions of 700°C to 720°C, stirring for 5 to 20 minutes, and keeping warm for 20 to 30 minutes, removing slag and filtering, and casting at 720°C to 740°C to obtain alloy ingots; 3) taking the alloy prepared in step 2), homogenizing it at 450-470°C for 7.5-8.5h, and quenching it with water to room temperature; 4) Extrusion alloy ingot molding, the casting temperature is 510-530℃, the mold temperature is controlled between 450-480℃, the extrusion speed is 1.5-2.5 / m·min-1, and the extrusion ratio is 32-35; 5) performing a solution treatment at 410-420° C. for 2-3 hours, and finally performing an intermittent aging treatment to obtain the high-strength and high-thermal-conductivity magnesium alloy.

[0014] In some examples, the intermittent aging treatment is implemented by: pre-aging the alloy at 150-160° C. for 10-12 hours, then water-cooling to room temperature, and then aging the alloy at 200-210° C. for 20-22 hours.

[0015] In a third aspect, the present invention provides a magnesium alloy casting, which is prepared from the high-strength and high-thermal conductivity magnesium alloy described in the first aspect.

[0016] The beneficial effects of the present invention are: In view of the problems of low strength and poor thermal conductivity of traditional magnesium alloys, the present invention has invented a high-strength and high-thermal-conductivity magnesium alloy containing microalloying elements Cu, Si, Ag and transition element Co. The alloy has high strength, good properties and excellent thermal conductivity, and has great application value in realizing the integration of magnesium alloy structure and function.

[0017] The high-strength magnesium alloy of the present invention mainly increases the Cu content in the alloy. When the Cu content in the alloy is between 2.8% and 3.3%, the Mg formed by Cu and Mg 2 Cu phase is a laves phase with high symmetry, which can effectively improve the strength, hardness, heat resistance and wear resistance of magnesium alloy. 2 Cu phase is dispersed in the metal matrix as hard particles, which can significantly improve the hardness and strength of magnesium alloy. These particles can hinder dislocation movement and increase the tensile strength and yield strength of the material. And as laves phase, it has the characteristics of high temperature resistance, so it can still maintain a high material strength in high temperature environment. In addition, part of Cu is dissolved in the β phase of magnesium alloy, which strengthens it and can further improve the strength of the alloy.

[0018] Adding 4.4~5.8% Si can generate Mg with Mg after alloy aging. 2 Si phase is a common strengthening phase in magnesium alloys. It can make magnesium alloys have excellent tensile properties and elongation under natural aging state, and at the same time give the alloy excellent wear resistance.

[0019] Adding 1.2~2.4% Co can significantly promote the nanoscale Mg 2The precipitation of Co dispersed phase can pin the grain boundary, inhibit the growth and recrystallization of grains, and hinder the movement of dislocations, thus comprehensively improving the strength of the alloy. At the same time, the addition of Co and Si can form a protective oxide film on the surface of the magnesium alloy, reducing the corrosion rate of the magnesium alloy in air or moisture, thereby improving its corrosion resistance.

[0020] Adding 1.3%~2.0% Ag to the alloy can significantly optimize the mechanical properties and thermal conductivity of the alloy while controlling the cost. Adding Ag can generate Mg-Ag eutectic in magnesium alloy. The formed phase has the characteristics of fine dispersion, making the structure of the alloy fine and uniform, and the fine and stable second phase is dispersed in the matrix, which can effectively hinder the basal plane dislocation slip and improve the mechanical properties of the alloy. The fine and dispersed eutectic phase distributed in the magnesium matrix can ensure the continuity of the magnesium matrix, will not hinder the migration of free electrons and phonons, reduce the scattering of electrons and phonons, and can greatly improve the thermal conductivity of magnesium alloy.

[0021] The intermittent aging process of the alloy can promote the precipitation of the alloy phase in different forms at different stages. In the pre-aging stage, the strengthening phase Mg is preferentially precipitated in the alloy. 2 Si and Mg 2 Cu phase. Mg 2 The Cu phase is more evenly distributed in the magnesium alloy matrix, reducing the Mg 2 The stress concentration or precipitation agglomeration caused by excessive Cu precipitation phases can reduce the crack propagation and material fatigue caused by stress concentration while achieving the optimal mechanical properties of the material, greatly increasing the service life of the alloy. 2 Si phase can greatly improve the hardness and wear resistance of the alloy. Mg will precipitate in the alloy during the aging stage. 2 Co phase and Mg-Ag eutectic phase can inhibit grain growth and recrystallization, and have a great effect on improving the strength and thermal conductivity of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the scanning electron microscope microstructure of the alloy in Example 2.

[0023] Figure 2 This is the scanning electron microscope microstructure of the alloy in Example 5. DETAILED DESCRIPTION

[0024] The following disclosure provides many different embodiments or examples for implementing different solutions of the present invention.

[0025] The present invention is described in detail below in conjunction with examples, comparative examples and experimental data, but is not intended to identify the key or decisive elements of the present invention or to limit the scope of protection.

[0026] The following disclosure provides many different embodiments or examples for implementing different solutions of the present invention.

[0027] The present invention is described in detail below in conjunction with examples, comparative examples and experimental data, but is not intended to identify the key or decisive elements of the present invention or to limit the scope of protection.

[0028] The chemical composition weight percentage of the alloy in each embodiment is Al 5.8-6.4%, Cu 2.8-3.3%, Zn 0.9-1.2%, Si 4.4-5.8%, Co1.2-2.4%, Ag 1.3%-2.0%. The raw materials are selected from industrial pure Mg ingot (purity ≥ 99.9%), industrial pure Al ingot (purity ≥ 99.5%), pure Zn (purity ≥ 99.5%), Mg-Si master alloy, Mg-Co master alloy, and Mg-Ag master alloy. The specific composition of each example is shown in Table 1.

[0029] Table 1 Chemical composition of the embodiments and comparative examples (mass percentage)

[0030] The preparation method of the alloy in each embodiment of the present invention is as follows: 1) Raw material preparation: Weigh pure Mg, Al, Zn ingots, Mg-Co, Mg-Si, Mg-Cu, Mg-Ag master alloys in proportion as raw materials for smelting.

[0031] 2) Melting and casting: Put the aluminum, magnesium, zinc ingots, aluminum master alloy and transition metal prepared in step 1) into the melting furnace, heat and melt, remove the slag and stir evenly, use SO 2 and N 2 The mixed protective gas is refined, the slag is removed, the mixture is allowed to stand for filtration, and the alloy ingot is cast; 3) Homogenization: The alloy ingot prepared in step 2) is subjected to homogenization annealing and solution heat treatment.

[0032] 4) Extrusion: Extrusion is performed according to the die according to the set extrusion process parameters; 5) Solid solution treatment: Take the alloy extrusion material from step 4) and perform solid solution treatment; 6) Intermittent aging: The alloy that has been subjected to solid solution treatment is subjected to an intermittent aging process to obtain the high-strength copper-containing magnesium alloy.

[0033] Wherein, the alloy melting temperature is 740-780°C; the refining temperature is 700-720°C; and the casting temperature is 720-740°C.

[0034] Wherein, the homogenization treatment temperature is 450-470°C, and the homogenization heat treatment time is 8h.

[0035] Among them, the casting temperature is 510~530℃, the mold temperature is controlled between 450~480℃, the extrusion speed is 1.5~2.5 / m·min-1, and the extrusion ratio is 32; The solution treatment temperature is 410°C and the temperature is kept for 2 hours; The intermittent aging process is to pre-age the alloy at 150°C for 10 hours, water cool the alloy to room temperature, and then age the alloy at 200°C for 20 hours. The total intermittent aging time is 30 hours.

[0036] The discontinuous aging process parameters of each embodiment and comparative example are shown in Table 2.

[0037] Table 2 Intermittent aging process parameters of the embodiments and comparative examples

[0038] Multiple refining agents and degassing agents can be added during the smelting process. Multiple refining agents and degassing agents are commonly used in the field, and the mass ratio of refining agent to smelting ingredients is (1-3):100. The composition of the multiple composite refining agent includes: 20wt% NaCl, 20wt% KCl, 35wt% NaF, 25wt% LiF; the mass ratio of degassing agent to smelting ingredients is 1:100, and the degassing agent is argon. Multiple refining agents and degassing agents themselves have little effect on the properties of the alloy.

[0039] Comparison of properties of magnesium alloys containing different copper The alloys obtained in the examples and comparative examples were tested for performance and mechanical properties. The test methods for strength and elongation were determined in accordance with GB / T 228.1-2010 "Metallic material tensile test Part 1: Room temperature test method"; the test method for metal thermal conductivity was determined in accordance with GB / T3651-2008 "Method for measuring thermal conductivity of metals at high temperatures". The performance test results of each example and comparative example are shown in Table 3.

[0040] Table 3 Performance test results of various embodiments and comparative examples

[0041] like Figure 1 As shown, Figure 1 The second phase is the Chinese character-shaped β phase commonly found in AZ61 magnesium alloy.

[0042] like Figure 2 As shown in the figure, the addition of Cu, Ag and Co elements can hinder recrystallization and grain growth, making the grains a mixed structure of Chinese character shape and granular shape, thereby improving the substructure strengthening ability of the alloy.

[0043] In summary, the present invention controls the content of Cu elements and Si, Co, and Ag elements and optimizes the heat treatment process to refine the grains in the alloy, improve the continuity of the magnesium alloy matrix, and form a second phase that improves the thermal conductivity of the material, thereby giving the alloy higher toughness and excellent thermal conductivity, which can be used to make metal parts in the fields of communication engineering, aerospace, etc. The high-strength magnesium alloy provided by the present invention has a tensile strength of ≥400MPa, an elongation of ≥20%, and a thermal conductivity of up to 140-145W / (m·K), and a density of about 1.8g / cm 3 .

[0044] The above is a further detailed description of the present invention, which should not be regarded as a limitation on the specific implementation of the present invention. For ordinary technicians in the technical field to which the present invention belongs, simple deduction or replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A high-strength and high-thermal-conductivity magnesium alloy, characterized in that: The magnesium alloy comprises, by mass percentage, 5.8% to 6.4% Al, 2.8% to 3.3% Cu, 0.9% to 1.2% Zn, 4.4% to 5.8% Si, 1.2% to 2.4% Co, 1.3% to 2.0% Ag, and the remainder is Mg and unavoidable impurity elements.

2. The magnesium alloy according to claim 1, characterized in that In terms of mass percentage, the Si content is 4.8-5.2%.

3. The magnesium alloy according to claim 1, characterized in that In terms of mass percentage, the content of the transition element Co is 1.9-2.2%.

4. The magnesium alloy according to claim 1, characterized in that In terms of mass percentage, the Ag content is 1.6-1.8%.

5. The magnesium alloy according to any one of claims 1 to 4, characterized in that: The alloy comprises, by mass percentage, 5.8-6.4% Al, 2.8-3.3% Cu, 0.9-1.2% Zn, 4.8-5.2% Si, 1.9-2.2% Co, 1.6-1.8% Ag, and the remainder is Mg and unavoidable impurity elements.

6. The magnesium alloy according to claim 5, characterized in that: In terms of mass percentage, the alloy comprises 5.99% Al, 3.20% Cu, 1.19% Zn, 5.28% Si, 2.04% Co, 1.74% Ag, and the remainder is Mg and inevitable impurity elements.

7. The magnesium alloy according to claim 1, characterized in that The high-strength copper-containing magnesium alloy has a yield strength of ≥320 MPa, a tensile strength of ≥400 MPa, an elongation of ≥20%, and a corrosion rate of ≤0.25 mm·y -1 The room temperature thermal conductivity can reach 140-145 W / (m·K), and the density is about 1.8 g / cm 3 .

8. The method for preparing a high-strength and high-thermal-conductivity magnesium alloy according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) Weigh the raw materials in proportion and smelt them at a temperature of 740℃~780℃, remove the slag and stir evenly; 2) Refining is performed under protective atmosphere conditions of 700°C to 720°C, stirring for 5 to 20 minutes, and keeping warm for 20 to 30 minutes, removing slag and filtering, and casting at 720°C to 740°C to obtain an alloy ingot; 3) taking the alloy prepared in step 2), homogenizing it at 450-470°C for 7.5-8.5h, and quenching it with water to room temperature; 4) Extrusion alloy ingot molding, the casting temperature is 510-530℃, the mold temperature is controlled between 450-480℃, and the extrusion speed is 1.5-2.5 / m·min -1 , extrusion ratio is 32-35; 5) performing a solution treatment at 410-420° C. for 2-3 hours, and finally performing an intermittent aging treatment to obtain the high-strength and high-thermal-conductivity magnesium alloy.

9. The preparation method according to claim 8, characterized in that: The implementation method of the intermittent aging treatment is: pre-aging the alloy at 150-160° C. for 10-12 hours, then water-cooling to room temperature, and then aging the alloy at 200-210° C. for 20-22 hours.

10. A magnesium alloy casting, characterized in that: The magnesium alloy is prepared from the high-strength and high-thermal-conductivity magnesium alloy according to any one of claims 1 to 7.